D. Heywood Hardy papers - Hardy, D. Heywood (Dermot Heywood), 1893-1982.
Correspondence, diaries, reports, speeches, notes, newspaper clippings, printed material, and other papers pertaining to Hardy's war service in Petrograd (Saint Petersburg), Russia, in 1917-1918 with the American Red Cross Mission to Russia. Hardy described conditions in Russia, beginning stages of the Bolshevik revolution, inspections and arrests by the Red Guard, the work of the Red Cross, and his social activities in Petrograd.
Library of Congress Prints and Photographs Division.
Lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: American Red Cross Mission to Russia; World War, 1914-1918 -- War work -- Red Cross; World War, 1914-1918 -- Russia; Saint Petersburg (Russia) -- Social life and customs; Saint Petersburg (Russia) -- History -- 1917-; Soviet Union -- History -- Revolution, 1917-1921.; Lawyers